2007
DOI: 10.1103/physrevd.75.124013
|View full text |Cite
|
Sign up to set email alerts
|

Domain walls as probes of gravity

Abstract: We show that domain walls are probes that enable one to distinguish largedistance modified gravity from general relativity (GR) at short distances. For example, low-tension domain walls are stealth in modified gravity, while they do produce global gravitational effects in GR. We demonstrate this by finding exact solutions for various domain walls in the DGP model. A wall with tension lower than the fundamental Planck scale does not inflate and has no gravitational effects on a 4D observer, since its 4D tension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 34 publications
4
67
3
Order By: Relevance
“…entering (14)(15) are all equal to each other. Note that for a given ansatz, the constancy of the traces (or of the eigenvalues) is a frame independent notion.…”
Section: Exact Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…entering (14)(15) are all equal to each other. Note that for a given ansatz, the constancy of the traces (or of the eigenvalues) is a frame independent notion.…”
Section: Exact Solutionsmentioning
confidence: 99%
“…that it would not be seen in exact solutions of the theory, but only shows up as an artifact of the linearization procedure [9]. While this seems problematic in non linear massive gravity [10,11], there is some evidence that it does work in DGP gravity [12,13,14]. It is then of some importance to better understand exact solutions of various types of massive gravities, among which bigravity theories.…”
Section: Introductionmentioning
confidence: 99%
“…If we let m 6 ! 1, thereby effectively decoupling the sixth dimension and turning off the cubic terms in (8), then (18) reduces to À 0 ¼ Ã=2M Þy þ c. For à > 0, as assumed above, the integration constant c must be positive since must always be positive (since it is the coefficient of R 5 in the action). Hence inevitably vanishes at some finite value of y in this case, indicating strong coupling.…”
Section: Obtaining Flat Brane Solutions For Any Tensionmentioning
confidence: 99%
“…The Dvali-Gabadadze-Porrati (DGP) model [6], in particular, takes this idea to the extreme and considers our 4D Universe to be embedded in an empty 5D bulk of infinite extent. Despite being observationally disfavored [7][8][9][10], 1 the normal branch of the DGP model is perturbatively ghost-free, in contrast to the selfaccelerating branch [14][15][16][17][18][19], and thus represents a perturbatively consistent infrared modification of gravity in which the graviton has a soft mass.…”
Section: Introductionmentioning
confidence: 99%
“…The metric above is actually closely related to the domain-wall solutions studied recently in [8]. In that case it was found that for a domain wall the metric is just the metric of a codimension two object in 5D, i.e.…”
Section: Lorentz Violation In Dgpmentioning
confidence: 90%